Detecting a response to weak sea breezes in the New South Wales coastal ocean - Mark T. Gibbs (New Zealand Journal of Marine and Freshwater Research, 2000)
Current meter data from the coastal ocean at Sydney, south‐eastern Australia, were analysed to seek evidence of a response to the prevailing summer sea breeze. A response to the sea breeze was found in the currents. This is significant since the magnitude of the sea breeze was small by comparison with winds associated with large‐scale pressure systems and the East Australian Current. Responses were determined by analysing short periods (3–5 days) of sea breeze activity as opposed to the whole 2‐month data set. The correlations between the alongshore nearshore diurnal‐period currents and the local wind stress during the sea breeze periods were significantly higher than the correlations during non‐sea‐breeze periods. Despite the stronger correlations the sea breeze could only account for around one‐quarter of the variance in the diurnal‐period currents. However, the detection of the response to the sea breeze is significant since the sea breeze has never previously been identified as a process for forcing alongshore nearshore currents on this shelf.